Shuplyak – historian-Germanist - Astroha, Viktar A. (Journal of the Belarusian State University. History, 2018)
Analyzes the scientific work of professor of the department of the modern and contemporary history of the faculty of history of the Belarusian State University P. A. Shuplyak. Considers the place and role of scientist in the development of Belarusian historiography of the modern history of Germany. The characteristic of the evolution of the researcher’s scientific views on the history of German foreign policy, its workers and the revolutionary trade union movement in the 1920–1930s, the history of the Weimar Republic, the activities of German political parties is given.
Keywords: Belarusian historiography; German studies; Modern history of Germany; Trade Union and workers’ movement; Weimar Republic, political parties of Germany